2005
DOI: 10.1111/j.1445-2197.2005.03400.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Total Knee Arthroplasty on Recreational and Sporting Activity

Abstract: The present study has shown that patients are adopting lower impact activities to participate in after TKA. The total number of patients performing a sport decreases postoperatively and the total amount of sport played decreases. These data will help to counsel patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
3
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 8 publications
8
74
3
9
Order By: Relevance
“…Similar to our findings, Chatterji et al [5] reported that those who did more sports before TKA were more active postoperatively (r = 0.482, p \ 0.001). One explanation is that patients performing sports before surgery were more likely to return to sports because they were motivated to participate in athletic activity in the first place.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to our findings, Chatterji et al [5] reported that those who did more sports before TKA were more active postoperatively (r = 0.482, p \ 0.001). One explanation is that patients performing sports before surgery were more likely to return to sports because they were motivated to participate in athletic activity in the first place.…”
Section: Discussionsupporting
confidence: 81%
“…Not significantly worse were the levels of megaprosthetic methods of the knee and hip. These findings were in line with previous studies about sports activity and elective joint arthroplasty of the hip and the knee [5], in which patients returned to moderate sports levels. Some patients after implantation of megaprostheses of the proximal femur, distal femur, and proximal tibia were able to practice sports not even recommended by the Hip and Knee Society Survey 2005 (skiing, jogging) for THA and TKA [17].…”
supporting
confidence: 92%
“…Naal et al [26] reported a return to activity rate of 95 % 18 months after the [17] reported a return to activity rate of 96.7 % 22 months after implantation of the medial Oxford UKA as well. In general, these reported return to activity rates are much higher when compared to rates demonstrated after TKR [3,8,17,25,33].…”
Section: Discussionmentioning
confidence: 65%